Antitumor Effects of Saffron-Derived Carotenoids in Prostate Cancer Cell Models. (11th May 2014) - Festuccia, Claudio; Mancini, Andrea; Gravina, Giovanni Luca; Scarsella, Luca; Llorens, Silvia; Alonso, Gonzalo L.; Tatone, Carla; Di Cesare, Ernesto; Jannini, Emmanuele A.; Lenzi, Andrea; D'Alessandro, Anna M.; Carmona, Manuel
Abstract : Crocus sativus L. extracts (saffron) are rich in carotenoids. Preclinical studies have shown that dietary intake of carotenoids has antitumor effects suggesting their potential preventive and/or therapeutic roles. We have recently reported that saffron (SE) and crocin (CR) exhibit anticancer activity by promoting cell cycle arrest in prostate cancer (PCa) cells. It has also been demonstrated that crocetin esters are produced after SE gastrointestinal digestion by CR hydrolysis. The aim of the present report was to investigate if SE, crocetin (CCT), and CR affected in vivo tumor growth of two aggressive PCa cell lines (PC3 and 22rv1) which were xenografted in male nude mice treated by oral gavage with SE, CR, and CCT. We demonstrated that the antitumor effects of CCT were higher when compared to CR and SE and treatments reverted the epithelial-mesenchymal transdifferentiation (EMT) as attested by the significant reduction of N-cadherin and beta-catenin expression and the increased expression of E-cadherin. Additionally, SE, CR, and CCT inhibited PCa cell invasion and migration through the downmodulation of metalloproteinase and urokinase expression/activity suggesting that these agents may affect metastatic processes. Our findings suggest that CR and CCT may be dietary phytochemicals with potential antitumor effects in biologically aggressive PCa cells.